Transcriptome profiling and phytohormone responses of Arabidopsis roots to different ambient temperatures. Issue 1 (1st January 2019) - Fei, Qionghui; Liang, Liyuan; Li, Fan; Zhang, Li; Li, Youxia; Guo, Yuman; Wu, Lei; Meng, Xueqin; Gao, Huanhuan; Li, Xiaofeng
ABSTRACT: Ambient temperatures influence plant growth and development, however very little is known about changes in root growth in response to ambient temperature change. Here, we performed transcriptome profiling and compared the differences in gene expression at lower and higher temperatures compared with normal plant growth temperatures. Our analysis of the biological processes and molecular functions regulated by differentially expressed genes revealed that low temperature upregulated carbohydrate metabolism and transmembrane transport, and downregulated signal transduction and defense. High temperature upregulated metabolic processes, transport, and auxin biosynthesis, and downregulated catabolic processes. We found that increased temperature specifically affected the levels of Arabidopsis response regulators, ARR1 and ARR12, to decrease cytokinin signaling, altered the level of the brassinosteroid receptor BRI1 to downregulate brassinosteroid signaling, and changed the level of the gibberellin receptor DELLA to upregulate gibberellin signaling and mediate root elongation. These data contribute to our knowledge of how root growth adapts to elevated ambient temperature under climate warming.